Peranan Permainan Tradisional Dalam Meningkatkan Kontrol Diri Anak Usia 6-8 Tahun - Nastiti Murdaningrum; Gregorius Ari Nugrahanta (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2021)
The purpose of this research was to develop a manual for traditional games in order to develop self-regulation character of children aged 6-8 years. The method used in this research was Research and Development (R&D). The results showed that a manual traditional games to develop self-regulation characters of children aged 6-8 years was developed based on ADDIE steps, the steps was Analyze, Design, Develop, Implement, and Evaluate. The quality of the manual for tarditional games showed the mean of “3,88” which was included in “Generally excellent” category with a recommendation